Terrestrial vertebrate fauna in a multifunctional landscape in Gabaldon, Nueva Ecija, Philippines - PAUL HENRIC P. GOJO-CRUZ; JENNIFER C. CALDITO; YVONNE DAPHNEY L. CATUBIG; HAYDEE MAY CORNES; JEANY S. CORPUZ; SHAINA S. MANIQUIZ; KAREN GAY E. MATUNAN; FRANCE JOSEPH PASCUAL; EAJAY S. SAN MIGUEL; GEOWENA C. SIGUANCIA; DANICA CARLA TURQUEZA; JAYSON P. MADLAO; CORNELIO FRANCIS CRUZ; JAY G. MERCULIO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Gojo-Cruz PHP, Caldito JC, Catubig YDL, Cornes HM, Corpuz JS, Maniquiz SS, Matunan KGE, Pascual FJ, Miguel ESS, Siguancia GC, Turqueza DC, Madlao JP, Cruz CF, Merculio JG. 2024. Terrestrial vertebrate fauna in a multifunctional landscape in Gabaldon, Nueva Ecija, Philippines. Biodiversitas 25: 583-597. This study was done to document the vertebrate fauna in a multifunctional landscape at the foothills of Mt. Mingan, Gabaldon, Nueva Ecija. The inventory of wild vertebrate fauna associated with the different habitat types in the area will be valuable in creating suitable management programs to reduce the impact of human activities in the area without affecting local economic activities. Standard survey techniques, including day and night transect walks, opportunistic surveys, mist-netting, and cage trapping, were employed to document vertebrate fauna in the agro-forest, around built-up areas, forest edges, lowland forest, grassland, and riparian habitats. A total of 79 species of vertebrate fauna were recorded, including 7 species of mammals, 13 species of reptiles, 9 species of amphibians, and 50 species of birds. Thirty-three (33) species were endemic to the Philippines. Regarding conservation status, eight (8) species were listed in the higher threat status under DAO 2019-09. Species richness was observed to be highest in lowland dipterocarp forests. On the other hand, species composition varies between habitats, with endemic species being more common in complex habitats such as lowland dipterocarp forests than in simpler habitats like agricultural areas. The high species richness and the presence of endemic and threatened species in the multifunctional landscape of the area highlight the need for management plans considering habitat heterogeneity and connectivity.